Population Pharmacokinetics and Exposure–Response Relationship of Carfilzomib in Patients With Multiple Myeloma. (7th December 2016) - Ou, Ying; Doshi, Sameer; Nguyen, Anh; Jonsson, Fredrik; Aggarwal, Sanjay; Rajangam, Kanya; Dimopoulos, Meletios A.; Stewart, A. Keith; Badros, Ashraf; Papadopoulos, Kyriakos P.; Siegel, David; Jagannath, Sundar; et al.
Abstract: A population pharmacokinetic (PK) model and exposure–response (E‐R) analysis was developed using data collected from 5 phase 1b/2 and 2 phase 3 studies in subjects with multiple myeloma. Subjects receiving intravenous infusion on 2 consecutive days each week for 3 weeks (days 1, 2, 8, 9, 15, and 16) in each cycle at doses ranging from 15 to 20/56 mg/m 2 (20 mg/m 2 in cycle 1 and, if tolerated, escalated to 56 mg/m 2 on day 8 of cycle 1). The population PK analysis indicated that among all the covariates tested, the only statistically significant covariate was body surface area on carfilzomib clearance; however, this covariate was unlikely to be clinically significant. Despite inclusion of different populations (relapsed or relapsed/refractory), treatments (carfilzomib monotherapy or combination therapy), infusion lengths (2 to 10 minutes or 30 minutes), and different doses, the E‐R analysis of efficacy showed that after adjusting for baseline characteristics, higher area under the concentration–time curve was associated with improved overall response rate (ORR), from 15 to 20/56 mg/m 2 . No positive relationships between maximum concentration and ORR were identified, indicating that ORR would not be expected to be impacted by infusion length. For safety end points, no statistically significant relationship between exposure and increasing risk of adverse events was identified. The results of an E‐R analysis provided strong support for a carfilzomib dose at 20/56 mg/m 2 as a 30‐minute infusion for monotherapy and combination therapy. This article illustrates an example of application of E‐R analysis to support labeling dose recommendation in the absence of extensive clinical data.